Sodium sorption and desorption in riparian soils impacted by road salt application - Luana G.G. Camelo; Tim P. Duval (Geoderma)
Sodium chloride (NaCl) is regularly used as road salt in cold regions to improve road safety during icy conditions. Once these ions enter the environment, Na is stored in the soils, with high concentrations of it leading to soil structure deterioration, organic matter leaching, and nutrient displacement. These impacts raise concerns about potential road salt effects in riparian soils, as these soils come into contact with direct runoff from urban areas and elevated Na levels in streams. Aiming to quantify the retention and release of Na in these ecosystems, this study evaluated Na sorption and desorption mechanisms of 18 different riparian soil types. The adsorption process followed a Langmuir isotherm within the tested concentration range (0–4800 mg Na/L) with deviation from linearity starting at ∼600 mg Na/L. The soils retained Na at the expense of other cations (Ca, Mg, and K), with maximum adsorption capacities ranging from 4000 to 13,700 mg Na/kg. Na build up in riparian soils is mostly driven by organic matter content, with clay and initial Na levels contributing to a lesser extent. Significant proportions of this adsorbed Na (>65 %) readily desorbed back into solution in the controlled experiments, illustrating the highly dynamic association of Na with soil components. These findings suggest that the first flushes following the road salt application season may mobilize previously retained Na in the field. The net effect of this behavior may be a recurring desorption and leaching of essential macronutrients from the soil.